A Bioinspired Fibrous Helix with Periodic Gradient for Directional Fluidic Gates. Issue 9 (16th February 2022) - Gao, Lei; Guo, Fengyun; Li, Ni; Wang, Yan; Guo, Ziyi; Xiong, Jie; Zhao, Yong
Abstract : Liquid transport is of great significance to industry and life, such as microfluidic chip, liquid separation, fluidic gates, and tissue fluid discharge. However, there are still some challenges to achieve well‐controlled directional transports, and the delamination often occurs for the now existing Janus membranes. Herein, fibrous assembly with hierarchically fibrous helix architecture bioinspired by tendrils through electrospinning combined with mechanical twisting technology is engineered and demonstrated. The liquid transport behavior using as fluidic gates by connecting light‐emitting diode (LED) and the resulting liquid separation mechanism were characterized and investigated, respectively. Different from previous materials, due to the existence of distinct periodic alternate gradient interface topology, the hierarchically fibrous helix exhibits a long‐range order and directional liquid transport trajectory as well as improved water management property. This strategy is cost‐effective and can be extended to other fields. The resultant materials are highly promising for applications in actuators, microfluidic chips, and fluidic gates. Abstract : Herein, bioinspired by natural tendrils, a hierarchically fibrous helix is prepared by facile electrospinning combined with mechanical twisting technology for unusual liquid transport. Different from traditional fibrous yarn, due to the periodic hydrophilic/hydrophobic alternately gradient structure, the as‐prepared composite fibrous helix can separate oil–water mixture rapidly and be used for fluidic gate.